FROM TRAINING TO TRANSFORMATION: ASSESSING THE SOCIO-ECONOMIC IMPACT OF SBI RSETIS ON SC/ST YOUTH IN RURAL TELANGANA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This research paper investigates the socio-economic impact of State Bank of India's Rural Self Employment Training Institutes (SBI RSETIs) on Scheduled Castes (SC) and Scheduled Tribes (ST) youth in rural Telangana. Addressing a critical gap in the literature, the study aims to empirically assess how vocational training programs influence employment rates, income levels, skill acquisition, self-esteem, and community engagement among marginalized communities. Employing a mixed-methods approach, the research combines quantitative data analysis with qualitative insights to offer a comprehensive evaluation of the program's outcomes. Data were collected through a structured survey involving 250 former SBI RSETI participants, analyzed using SPSS for quantitative findings and thematic analysis for qualitative feedback. Key findings reveal significant improvements in employment rates and income levels post-training, alongside notable gains in technical, entrepreneurial, and financial literacy skills. Participants also reported increased self-esteem and enhanced community engagement, highlighting the broader social benefits of vocational training. These outcomes underscore the effectiveness of SBI RSETIs in facilitating socio-economic upliftment and empowerment for SC/ST youth in rural areas. The study contributes to the discourse on rural development and vocational training, emphasizing the need for targeted educational programs as a vehicle for socio-economic transformation and inclusive growth. Implications for policy-makers and program designers underscore the importance of continuing support and expansion of vocational training initiatives to achieve sustainable development goals.